Health Education for the Prevention of Covid-19 Transmission with the 3M Movement in Ngaglik District, Batu City, East Java - Santy Irene Putri; Aris Widiyanto; Asruria Sani Fajriah; Joko Tri Atmojo; Prima Soultoni Akbar; Nur Laili Qomariah (Poltekkes Kemenkes Surakarta, 2021)
Background: WHO has officially decided Covid-19 as a pandemic. The Indonesian government has designated Covid-19 as a non-natural disaster in the form of a disease outbreak that needs to be addressed systematically in various ways, including involving all community members. In terms of the transmission pattern of Covid-19, which has spread in almost all regions of the province of Indonesia, the number of cases and the number of deaths is increasing every day and has an impact on health, political, social, economic, cultural and other aspects. Preventive action is a strategy to reduce the spread of Covid-19. The aim of this community service is that after receiving health education, people are aware the most important strategy is to use a mask, wash your hands and / or use a portable hand sanitizer (handsanitazier). Avoid touching their face and mouth after interacting with a potentially contaminated environment and keeping a distance from other people. Methods: Health education is carried out through lectures and discussions with the community using LCD media as well as leaflet distribution and distribution of masks by complying with health protocols such as participants using masks, maintaining distance and providing outdoor hand washing stations. The implementation of the activity begins with a pre-test, and ends with post-test measurements.The activity was carried out on January 2, 2021 with the target of all members of the community in Ngaglik District, Batu City, East Java. Results: As many as 20 participants were involved in the implementation of health education activities for the prevention of covid-19 transmission with the 3M movement. The activity can be carried out smoothly, the participants are enthusiastic and understand the material that has been delivered, it is proven when the presenter carries out the evaluation that the participants are able to answer the questions given well. Conclusion: health education activities for the prevention of covid-19 transmission with the 3M movement are effective in increasing public health insights and knowledge, creating public awareness to implement the 3M movement and self-awareness to adopt a clean and healthy lifestyle.